Biosystematic study in the genus Cousinia Cass. (Asteraceae), section Cousinia. (December 2016) - Minaeifar, Amir Abbas; Sheidai, Masoud; Attar, Farideh; Noormohammadi, Zahra; Ghasemzadeh-Baraki, Somayeh
Abstract: The genus Cousinia Cass. (Family Asteraceae) with about 600–700 species is distributed in central and western Asia. Iran has more than 200 Cousinia species that grow in mountainous areas. Cousinia is not monophyletic and with the genus Arctium, comprise the Arctium-Cousinia complex. The Cousinia species are distributed in 70 sections. The species relationship in the sect. Cousinia is not known, moreover, in few cases, inter-specific hybrids and intermediate forms are recognized. Therefore, we undertook a detailed morphological, micro-morphological and molecular (Cp-DNA and ISSRs) study of the section Cousinia with the following objectives: 1- to delimitate the species, 2- to identify potential intermediate forms, 3- to investigate the species inter-relationship. The present study revealed that combination of morphological, micro-morphological and ISSR data can delimit the species. We did not encounter any intermediate forms throughout the studied area. AMOVA and STRUCTURE analysis revealed that the species of this section are genetically differentiated but have some degree of shared common alleles. Reticulation analysis by T-REX also showed some degree of gene flow for Cp-DNA. This low degree of genetic and morphological variability in Cousinia, can help the species to cope with environmental variability they face. Highlights: The genus Cousinia Cass. (Family Asteraceae) with about 600–700 species is distributed in central and western Asia. We undertook a detailed morphological, micro-morphological and molecular (Cp-DNA and ISSRs) study of the section Cousinia with the following objectives: 1- to delimitate the species, 2- to identify potential intermediate forms, 3- to investigate the species inter-relationship. The present study revealed that combination of morphological, micro-morphological and ISSR data can delimit the species. AMOVA and STRUCTURE analysis revealed that the species of this section are genetically differentiated but have some degree of shared common alleles. Reticulation analysis showed some degree of gene flow for Cp-DNA that can help the species to cope with environmental variability they face.